Pengaruh Pertumbuhan Penduduk, Kemiskinan, Tingkat Pendidikan dan Upah Minimum Provinsi Terhadap Tingkat Pengangguran Terbuka di Propinsi Banten - Apriliana, Savira; Wijaya, Riko Setya (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
Banten Province is one of the provinces located on the island of Java with a relatively high level of economic activity. However, the high rate of open unemployment has become one of the hindering factors in the economic development of Banten Province. This research aims to determine the influence of population growth, poverty, education level, and provincial minimum wage on the open unemployment rate in Banten Province. The data used in this study are secondary data obtained from relevant authorities for the period of 2011-2021. The analytical method employed is multiple linear regression analysis. The research findings indicate that poverty and education level, individually, have a significant influence on the open unemployment rate in Banten province. On the other hand, population growth and provincial minimum wage, individually, do not have a significant influence on the open unemployment rate in Banten province. However, when considered collectively, population growth, poverty, education level, and provincial minimum wage have a significant influence on the open unemployment rate in Banten province simultaneously.